Indoor composting of vine by-products to produce substrates for mushroom cultivation - Pardo, A.=700 1 Perona, M.A.; Pardo, J.
(En, Es)
Ilus., 32 ref.
Keywords: AGARICUS BISPORUS; ELABORACION DEL COMPOST; MATERIA ORGANICA; MATERIA PRIMA; VID; ESPAÑA